2022
DOI: 10.1002/dta.3363
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of freebase nicotine and nicotine salts following subcutaneous administration in male rats

Abstract: Nicotine lactate, nicotine tartrate, nicotine benzoate, and freebase nicotine (FBN) are four forms of nicotine salt systems that are present in tobacco products. However, few in vivo studies have compared their pharmacological (pK) efficacies, which are important for understanding their roles in the addiction and abuse of tobacco and nicotine products. In this work, the pK of the above nicotine salt systems was studied by subcutaneously injecting their aqueous solutions in rats and obtaining blood samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Preclinical studies on the effect of formulation on metabolism are contradictory. One study conducted in rats found that following a single sub-cutaneous dose of nicotine freebase, serum nicotine levels were higher than those in rats injected with nicotine salts [ 6 ], which are consistent with the results of the current study. However, in another study, mice exposed to nicotine salt vapor had significantly higher serum cotinine levels than mice exposed to nicotine freebase.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Preclinical studies on the effect of formulation on metabolism are contradictory. One study conducted in rats found that following a single sub-cutaneous dose of nicotine freebase, serum nicotine levels were higher than those in rats injected with nicotine salts [ 6 ], which are consistent with the results of the current study. However, in another study, mice exposed to nicotine salt vapor had significantly higher serum cotinine levels than mice exposed to nicotine freebase.…”
Section: Discussionsupporting
confidence: 91%
“…When studying the physiological, metabolic and behavioral effects of drugs of abuse it is imperative to take into consideration sex differences as well as delivery methods [ 6 , 8 ]. Previous preclinical studies have noted a difference in nicotine and cotinine serum levels in male and female mice exposed to nicotine, with males showing higher nicotine serum levels than females [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to highlight the possibility of a toxicological impact of increased aerosolization resulting from polydrug consumption through e‐cigarettes. In another study dealing with nicotine delivery, this time of an in vivo nature, Han et al 6 consider the importance of the form of nicotine (which is dependent on pH). In the tobacco leaf, nicotine exists in its salt form, and when it is extracted and purified to create pharmaceutical grade nicotine, it converts to its unprotonated or ‘freebase’ form.…”
mentioning
confidence: 99%
“…In the tobacco leaf, nicotine exists in its salt form, and when it is extracted and purified to create pharmaceutical grade nicotine, it converts to its unprotonated or ‘freebase’ form. Han et al 6 examine the pharmacokinetics of freebase nicotine compared with three salts (nicotine lactate, nicotine tartrate and nicotine benzoate). Following subcutaneous administration in rats, the authors found that freebase nicotine can reach higher blood concentrations and nicotine concentrations were sensitive to the pH of the preparations.…”
mentioning
confidence: 99%